Elimination disorder in children and adolescents: psychological treatment with behavioral and cognitive approach - Ivana Kreft Hausmeister; Valentina Stefanova Kralj (Psihološka Obzorja, 2023)
According to research the most appropriate time to begin toilet training is after child’s second birthday when he reaches control of pelvis floor and anal sphincter. However, a child has to first master certain skills which he will need for toilet training and that each child masters in its own time. That is also the reason why medical classifications define elimination disorder after 4th and 5th year of age. In international classification system DSM 5 elimination disorders are identified in two categories: enuresis and encopresis (American Psychiatric Association, 2013). When there are negative influences of enuresis or encopresis present children are usually referred to psychologists or after difficulties are revealed during a regular developmental examination. Overview of literature shows that behavioral therapy is one of the most effective treatments and some specific techniques will be presented in this article.